EFEKTIFITAS PENERAPAN MODEL CONTEXTUAL TEACHING LEARNING (CTL) DALAM PENINGKATAN KEMAMPUAN MENULIS PUISI - Suri, Murnia; Fajriati, Rafni; Fitriliana, Fitriliana; Mursyida, Citra Syifa (JOURNAL OF EDUCATION SCIENCE, 2025)
The problems faced by students at SDN 1 Lhok Kuala Baro in writing English poetry are caused by limited in vocabulary mastery. The application of Contextual Teaching and Learning (CTL) which involves the relationship between written themes and students’ daily experiences is assumed to make it easier for those to put together words and compose sentences. This study aims to describes the effectiveness of using this learning model and also aims to see the development of poetry writing skills toward the grade fourth students in SDN Lhok Kuala Baro. Data were collected through test and observations of 27 students and then analyzed descriptively using percentage techniques and the N-Gain test. The results obtained were that before the implementation of CTL only 16.6% students had achieved good score but after the implementation, the completion had increased to 76.9%. Meanwhile, the N-Gain test results showed an average of 0.571 with an increase of 57.1%, indicating the effectiveness of CTL in improving students’ writing skills. These findings shows that CTL can significantly improve students’ mastery, improve their imagination in expressing ideas and skilled in arranging words.Key words: Contextual Teaching Learning, Poetry Writing Skills